Some Transport Properties of γ-Cyclodextrin Aqueous Solutions at (298.15 and 310.15) K - Ribeiro, Ana C. F. (2008)
Values of binary mutual diffusion (interdiffusion) coefficients, obtained by using the Taylor dispersion method, for aqueous solutions of γ-cyclodextrin in the concentration range from (0.002 to 0.010) mol·dm−3 and temperatures (298.15 and 310.15) K are reported. From these experimental results, the hydrodynamic radius values for the γ-cyclodextrin are estimated. Also, the measured diffusion coefficients are used with both Hartley’s and Gordon’s equations to estimate activity coefficients for aqueous γ-cyclodextrin. These studies are complemented by some density and viscosity measurements, carried out at the same range of concentrations and temperatures. The effect of both the viscosity of the medium and the formation of γ-cyclodextrin dimers on the estimated hydrodynamic radius is discussed.